2014
DOI: 10.3923/ajbkr.2015.13.22
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Industrially Relevant Extracellular Pectinase from Aspergillus terreus NCFT 4269.10 Using Orange Peels as Substrate

Abstract: In this study, Aspergillus terreus NCFT4269.10 was selected for the biosynthesis of pectinase after screening from fifteen native fungal strains as the performance of A. terreus was best in pectin hydrolyzing activity (2.75 cm). Aiming at the cost effective fermentation, several agro-industrial residues such as, Pearl Millet (PM), Finger Millet (FM), Orange Peels (OP), Mustard oil Cake (MoC) and Chikling Vetch Peels (CVP) were evaluated for highest pectinase production using Liquid Static Surface Fermentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(23 reference statements)
0
1
1
Order By: Relevance
“…The reduction in enzyme production might be due to exhaustion of nutrient and metabolite accumulation in the medium (PALANIYAPPAN et al, 2009). Our findings are in contrast to SETHI et al (2015) who reported 96hours are optimal time period for the production of pectinase. The shorter fermentation period is more beneficial and increases the industrial importance of strain.…”
Section: Figure 1 Impact Of Different Fermentation Mediacontrasting
confidence: 99%
“…The reduction in enzyme production might be due to exhaustion of nutrient and metabolite accumulation in the medium (PALANIYAPPAN et al, 2009). Our findings are in contrast to SETHI et al (2015) who reported 96hours are optimal time period for the production of pectinase. The shorter fermentation period is more beneficial and increases the industrial importance of strain.…”
Section: Figure 1 Impact Of Different Fermentation Mediacontrasting
confidence: 99%
“…Similarly, maximum protein was also obtained from BP fermentation medium. Liquid shaking fermentation using orange peels by A. terreus at 120 rpm for 96 h at 30°C was suitable than static condition for pectinase biosynthesis (Sethi et al 2015). Out of these three agro waste (banana peels, wheat bran and saw dust) banana peel showed highest enzyme activity in both the fermentation process, hence, pectinase enzyme extracted from banana peel are used for further purification, ethanol production and apple juice clarification activity.…”
Section: Resultsmentioning
confidence: 99%